SOFTWARE FOR SPECTRAL ANALYSIS RIZOGRAF PRINT - P. E. Sulim; V. S. Yudenkov (Системный анализ и прикладная информатика)
The objective of this study is to develop a model rizograficheskoy based printing functions package IPT and automated profile selection rizograficheskoy printing. Work risograph for halftone printing consists of two stages – production of screen form (master film) and printing. The master film is supplied and installed in the printing machine in the form of rolls of different sizes, depending on the print size and model of the device. The capacity of the roll is measured in squares – segments of the printing material. Master-film for risograph consists of three layers: a solid but porous layer such as a paper web neprokleennogo and without fillers; an adhesive layer bonding the paper web to the upper layer; upper, thin polymer layer.